Effects of oxycodone on immune function in patients undergoing radical resection of rectal cancer under general anesthesia. Issue 31 (August 2017) - Cui, Jia-Hua; Jiang, Wan-Wei; Liao, Ya-Jing; Wang, Qing-Hui; Xu, Min; Li, Yu
Abstract : Abstract: This study aims to explore the effect of oxycodone hydrochloride injection on the immune function of patients who underwent radical resection of rectal cancer under general anesthesia. Eighty patients were enrolled and randomly divided into group A and B (n = 40, each). All patients underwent general intravenous anesthesia. At the end of surgery, each patient in group A was injected with 5 mg (5 mL) of oxycodone hydrochloride, while 5 mg (5 mL) of morphine hydrochloride in group B. Venous blood was withdrawn in both groups at different time points. Changes in the numbers of T lymphocyte subsets and natural killer (NK) cells were determined by flow cytometry. First the numbers of T lymphocyte subsets and NK cells at T1, T2, T3, and T4 decreased in both groups, compared with those at T0, and the differences were statistically significant. Furthermore, the numbers reduced to a minimum at T2 and began to recover at T3. Second the differences between group A and B at T1, T2, T3, and T4 were statistically significant; and the numbers of T lymphocytes and NK cells were higher in group A than in group B at corresponding time points. Oxycodone hydrochloride and morphine hydrochloride both have inhibitory effects on immune function in patients undergoing radical resection of rectal cancer after surgery. However, oxycodone hydrochloride has a smaller effect compared to morphine hydrochloride.